Band gap and mass renormalisation in GaIaP/AlGaInP quantum wells - Priest, A; Nicholas, R; Najda, S; Duggan, G; Kean, A (1998)
We report magneto-luminescence studies of dense electron-hole plasmas in compressively strained GaInP/AlGaInP quantum wells. At carrier densities of order 10(13) cm(-2) many-body effects are investigated. The band gap is reduced by up to 36 meV, much less than expected from conventional random phase approximation calculations. However, much better agreement is obtained on comparison with recent density functional calculations which include the Hartree energy. The reduced mass is found to increase by up to 40% over values from low-excitation measurements. Comparison with other work suggests that the mass renormalisation is substantial in materials with wide band gaps. (C) 1998 Elsevier Science B.V. All rights reserved.